THEMATIC-INTEGRATIVE PARADIGM OF CURRICULUM AND PAI LEARNING DEVELOPMENT IN MADRASAHS OR SCHOOLS (THEORETICAL STUDY) - Nurmasihin, Nurmasihin; Khadijah, Ifah; Suherman, Usep (Program Studi Pendidikan Agama Islam, 2025)
This study aims to examine the thematic-integrative paradigm in the development of curriculum and learning in Islamic Religious Education (PAI) at madrasahs or schools through a literature review approach. This paradigm offers a solution to the challenge of fragmented learning by integrating Islamic values into cross-subject themes in a contextual and holistic manner. The literature study method is used to analyze theories, concepts, and previous research findings relevant to the integrative approach in Islamic education. The findings indicate that the thematic-integrative approach enhances the effectiveness of PAI learning, supports value internalization, and shapes students' character in spiritual, intellectual, and social dimensions. The successful implementation of this paradigm is strongly influenced by teacher competence, institutional support, and the availability of adaptive curriculum tools. Therefore, strengthening teacher training and providing systemic support are key to realizing a more transformative and relevant PAI learning experience for today’s educational needs.